Investigating the “inverse care law” in dental care: A comparative analysis of Canadian jurisdictions - Dehmoobadsharifabadi, Armita (Can J Public Health, 2016)
OBJECTIVES: To compare physician and dentist visits nationally and at the provincial/territorial level and to assess the extent of the “inverse care law” in dental care among different age groups in the same way. METHODS: Publicly available data from the 2007 to 2008 Canadian Community Health Survey were utilized to investigate physician and dentist visits in the past 12 months in relation to self-perceived general and oral health by performing descriptive statistics and binary logistic regression, controlling for age, sex, education, income, and physician/dentist population ratios. Analysis was conducted for all participants and stratified by age groups - children (12–17 years), adults (18–64 years) and seniors (65 years and over). RESULTS: Nationally and provincially/territorially, it appears that the “inverse care law” persists for dental care but is not present for physician care. Specifically, when comparing to those with excellent general/oral health, individuals with poor general health were 2.71 (95% confidence interval [CI]: 2.70–2.72) times more likely to visit physicians, and individuals with poor oral health were 2.16 (95% CI: 2.16–2.17) times less likely to visit dentists. Stratified analyses by age showed more variability in the extent of the ‘inverse care law” in children and seniors compared to adults. CONCLUSIONS: The “inverse care law” in dental care exists both nationally and provincially/territorially among different age groups. Given this, it is important to assess the government’s role in improving access to, and utilization of, dental care in Canada.